PENGETAHUAN, SIKAP, DAN PRAKTIK MENGENAI HIGIENE PERSONAL SEBAGAI UPAYA PENCEGAHAN COVID-19 DI PROVINSI DKI JAKARTA - Kamila Nandita Zuriyanda; Yusniar Hanani Darundiati; Sulistiyani Sulistiyani (Jurnal Kesehatan Masyarakat (Undip), 2021)
COVID-19 is disease caused by SARS-CoV2 and becoming world concern because large number of cases and fast transmission between humans. Therefore, it is needed of knowledge, attitude, and practice of personal hygiene as primary pervention during COVID-19 pandemic. The purpose of this research is to find out the knowledge, attitude, and practice of personal hygiene as COVID-19 pervention in DKI Jakarta. This was descriptive research with cross-sectional study design. The data research was using googleform online questionnaire. Sample of this research are 150 respondents aged 15-29 years old in DKI Jakarta during COVID-19 pandemic. Data analysis using univariate and bivariate (chi square). Based on the research results, it was found that the majority of respondents had 51.3% moderate knowledge, 56% moderate attitudes, 84.7% moderate practice, and there was significant relationship between knowledge and attitudes (p-value=0,04) but there is no significant relationship between attitude and practice (p-value=0.086). It can be concluded that respondents already have moderate knowledge, attitudes, and practices regarding personal hygiene in the prevention of COVID-19. It’s hoped that the public will always follow the development of information regarding the prevention of COVID-19, especially regarding hand hygiene, the ethics of coughing or sneezing and practicing it in everyday life.